Improving Company Performance Analysis Based on Return on Assets and Return on Equity Ratio - Siti Aisyah; Ahmad Nur Budi Utama (IECON: International Economics and Business Conference, 2024)
Measurement of the company's financial performance is by using financial ratios. The company provides financial statement information to outside parties such as the capital market and the company provides signals to users of financial statements. This study was conducted to determine the effect of financial performance on company value both partially and simultaneously in manufacturing companies listed on the Indonesia Stock Exchange for the period 2020 to 2022, sample 74 company. The limitation or scope in this study is the effect of financial performance on company value in manufacturing companies listed on the IDX. The financial performance in question is seen from the financial ratios, namely ROA and ROE during 2020 to 2022. Using quantitative methods, it was found that ROA had no effect on company value. This can be seen from the t test that has been done, which shows that the independent variable, namely ROA, has a Sig. value of 0.154 which is greater than 0.05. Another case with ROE which has a Sig. value of 0.015 which is less than or less than 0.05, this indicates that only the independent variable ROE has an effect on the value of the company. The influence caused by these two ratio roles has a very low influence on the value of manufacturing companies on the IDX, which is 23.5%. From the test results, it can be seen that there are other factors of 76.5% that are used simultaneously have greater potential in influencing company value.